Postpartum Recurrent Mastitis Despite Resolution of Prior Prolactinoma - Pamela L. Alebna; Salman Samar; Mindy Griffith (Annals of Internal Medicine: Clinical Cases)
We present a 35-year-old woman with history of a prolactinoma who presented 11 weeks postpartum with recurrent mastitis. Per the patient, in the past she took cabergoline but stopped about 5 years previously. Despite attempts to wean, postpartum, she continued to express an excessive amount of breast milk. Magnetic resolution imaging revealed a slightly heterogeneous appearance of the pituitary gland, and she was started on dopaminergic agents. This case demonstrates that significant lactotroph hyperplasia can occur after breastfeeding ends despite the resolution of a prior prolactin-secreting microadenoma.